Meningkatkan Hasil Belajar Siswa Kelas 4 SD Terhadap Materi Beriman Kepada Rasul Allah Melalui Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) SDN 7 Muaro Bodi Kecamatan IV Nagari - Maulani, Popi Lestari (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve the interest and learning outcomes of grade IV students at SDN 7 Muaro Bodi on the material "Faith in the Messengers of Allah" by applying the cooperative learning model Numbered Heads Together (NHT) supported by interactive media. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The results of the study show that the application of the NHT model, complemented by interactive quizzes and creative assignments, successfully increased student engagement and learning outcomes. In the first cycle, student participation improved, although some students remained passive. However, in the second cycle, the use of more engaging media and student competition significantly enhanced participation and learning motivation. The average student scores also showed significant improvement, reaching the Minimum Completion Criteria (KKM). Therefore, the NHT learning model proved to be effective in improving the quality of Islamic Religious Education learning.